Termite diversity across an anthropogenic disturbance gradient in the humid forest zone of West Africa - Eggleton, P.; Bignell, D.; Hauser, S.; Dibog, L.; Norgrove, L.; Madong, B. (Elsevier, 2002)
Data are presented for termite assemblages across an anthropogenic disturbance gradient in the humid forest zone of West and Central Africa. Sampling was by standardised 100m × 2m transects in: primary forest, several ages of regenerating forest, agroforestry plots, short fallows, mixed food crop fields, and mechanically cleared plots. Most sites were in southernCameroon—two additional transects were conducted in primary forest in Congo (Brazzaville). Species richness was negatively correlated with the disturbance gradient, although transects in areas with a complete or near-complete canopy were broadly similar in species richness. The strongest negative correlation was found for termite species feeding furthest down the humification gradient (group IV soil feeders) probably because these species are energetically constrained from living in non-forest habitats. In contrast species feeding and nesting in dead wood (group I wood feeders) termites, which live in the most protected micro-habitats, were significantly positively correlated with the disturbance gradient. Species composition was also strongly correlated with disturbance level in multivariate redundancy analyses. Pest species were an insignificant element of the assemblage, in part because of the distance of the sites from savanna source pools. Overall, it appears that termite-mediated wood and litter decomposition may be relatively unaffected by light to moderate disturbance intensity, but that soil-conditioning by termites might be greatly reduced in agricultural land cleared from tropical forest.